Exploring Gendered Linguistic Features in Arabic and English: A Comparative Perspective - Safarova Zarnigor Zokhid’s daughter (Лучшие интеллектуальные исследования, 2024)
Annotation: This article examines the field of gender linguistics, which investigates the relationship between language and gender roles and stereotypes. It focuses specifically on how language shapes and maintains gender identities and how gender influences language usage. The article will compare and analyze the use of gendered language in Arabic and English phrases.